Adsorption and adhesion of common serum proteins to nanotextured gallium nitride1. Issue 6 (14th February 2015) - Bain, Lauren E.; Hoffmann, Marc P.; Bryan, Isaac; Collazo, Ramón; Ivanisevic, Albena
<x xml:space="preserve">Abstract</x> Morphology can be used to modulate the adsorption of proteins onto gallium nitride.